LONG-TERM INCIDENCE AND RISK FACTORS OF OCULAR HYPERTENSION FOLLOWING DEXAMETHASONE-IMPLANT INJECTIONS: THE SAFODEX-2 STUDY. Issue 7 (July 2021) - Rezkallah, Amina; Mathis, Thibaud; Abukhashabah, Amro; Voirin, Nicolas; Malclès, Ariane; Agard, Émilie; Lereuil, Théo; Denis, Philippe; Dot, Corinne; Kodjikian, Laurent
Abstract : Purpose: To analyze the incidence, risk factors, and time to onset of ocular hypertension (OHT) after intravitreal injections (IVI) of dexamethasone implant and to evaluate the long-term cumulative probability of intraocular pressure elevation. Methods: Eyes of patients having received at least one dexamethasone implant IVI between October 2010 and February 2015 were included in the present study. Ocular hypertension was defined as intraocular pressure > 25 mmHg and/or an increase of 10 mmHg over the follow-up period compared with baseline intraocular pressure. Results: Four hundred ninety-four eyes were studied in 410 patients. For a total of 1, 371 IVI, the incidence of OHT was 32.6% in the study eyes with a mean follow-up period of 30 months (3–62.5) and a median follow-up of 29 months. Pressure-lowering treatment was introduced for 36.9% of eyes. Topical treatment alone was sufficient to manage OHT in 97%. Young age, male sex, uveitis and retinal vein occlusion, and glaucoma treated with a double- or triple-combination topical pressure-lowering medication were found to be risk factors for OHT. The incidence of OHT did not change with an increase in the number of IVI, and there was no cumulative effect, defining by an increase of the incidence of OHT in patients after repeated IVI ( P = 0.248). Conclusion: This study confirmed that OHT is of moderate incidence, transient, controlled by topical treatment and provides data on the long-term cumulative probability of intraocular pressure elevation in a large cohort of eyes treated with dexamethasone implant IVI. Repeat injections of dexamethasone implant neither increase nor decrease the risk of OHT. Abstract : About one-third of the 494 eyes treated with dexamethasone implant experienced ocular hypertension, found to be transient and well-controlled by topical treatment in 97%. Its incidence did not change with an increase in the intravitreal injections number, thus confirming that regular intraocular pressure checks are important, as with any steroid.